Philosophers and Scholars Attributed to Petra in Classical Sources - Al-Salameen, Zeyad Mahdi (Jordan Journal for History and Archaeology, 2024)
The paper sheds light on a group of philosophers and scholars associated with Petra, despite the fact that most of them did not live there. They include: Gaius, Callinicus, Genethlius, Epiphanius, Gessius, and Dousarius. These pioneer scholars, whose works have unfortunately been lost, bore Greek names, wrote in Greek and were apparently followers of the sophistry doctrine. The research is based on a number of Roman and Byzantine sources. Among them is the Suda Lexicon, an encyclopedia dating back to the tenth century AD, based on several classical sources. These sources show that the Arab’s knowledge of Greek philosophy predates Islam by a significant period of time and confirm that some Arabs studied philosophical works thoroughly before Islam and played a significant role in disseminating certain philosophical and intellectual doctrines.